Nurturing Love and Tolerance Through Local Wisdom Tourism - Masruroh, Siti (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This research analyses the economic significance of the Siraman ritual at Sedudo Waterfall, Nganjuk, as a form of tourism based on local wisdom. The Siraman tradition, which is held every month of Suro, not only has spiritual and cultural significance, but also serves as an economic space that fosters social interaction and empowerment of the surrounding community. The purpose is to understand the contribution of this ritual to the local economy while preserving cultural values and Islamic ethics. The method used is descriptive qualitative with an ethnographic approach, through field observations, interviews with community leaders and local traders, and documentation. The results show the Siraman tradition is not only a religious and cultural celebration but also encourages economic empowerment through culinary trade, accommodation services, and tourism services. The conclusion is Siraman ritual represents a synergy between spiritual devotion, cultural preservation, and inclusive economic growth rooted in global love and harmony